Improving the Quality of Public Services Through Bureaucratic Reform at the Gunungsari District Office - Huddori, Huddori; Su’amah, Su’amah; Widayanti, Sri; Hendayani, Bq; Kartini, Kartini (JURNAL ILMIAH DETUBUYA, 2025)
This study aims to determine and analyze Bureaucratic Reform in Public Services at the Gunungsari District Office, West Lombok Regency, West Nusa Tenggara. The research method employed is qualitative, utilizing a case study approach. The theory used by the author is based on the guidelines outlined in Komarudin (2014:268), which include "Guidelines for Public Service Providers, Transparency and Accountability of Public Services, Public Service Standards, Guidelines for the Implementation of Public Services and Public Service Programs in Bureaucratic Reform." However, during its implementation, obstacles are still encountered, primarily due to work accountability that remains suboptimal, resulting in services not being completed within the specified timeframe and in accordance with applicable provisions. In order to continue to carry out consistent evaluations of bureaucratic reform in public services, build and develop a better organizational culture, carry out routine supervision, and improve the quality of Human Resources of the apparatus through training and education for all employees.